Revision of the Genera Diplocladus Fairmaire and Strotocera Schenkling (Coleoptera: Cleridae, Tillinae) - Gerstmeier, Roland; Weiss, Ingmar (Zootaxa, 2009)
The genera Diplocladus Fairmaire and Strotocera Schenkling are taxonomically revised. Thirty four species are recognized within this revision (11 Diplocladus, 23 Strotocera). Diplocladus tilloides Fairmaire, 1887 n. syn., and Diplocladus rhodesianus Péringuey, 1899 n. syn., are placed in synonymy with Diplocladus louvelii Spinola, 1844; Strotocera sjoestedti Schenkling, 1908 n. syn., is synonymized with Strotocera convexa Hintz, 1905; Strotocera multisignata Pic, 1926 n. syn., is synonymized with Strotocera emerita Péringuey, 1899; Strotocera orangica Kuwert, 1893 n. syn., is synonymized with Strotocera versicolor Chevrolat, 1842 and Strotocera unimaculata Pic, 1953, n. comb., n. syn., is synonymized with Diplocladus discoidalis Schenkling, 1908. The following species are described as new taxa: Diplocladus arabicus, Diplocladus bipunctatus, Diplocladus compactus, Diplocladus ebureofasciatus, Diplocladus nigrinus, Diplocladus rufobasalis, Strotocera auratopilosa, Strotocera bartletti, Strotocera brevefasciata, Strotocera chicoi, Strotocera elegantula, Strotocera mawdsleyi, Strotocera minuscula, Strotocera roberti, Strotocera rufoapicalis, Strotocera similis, Strotocera topolinae, Strotocera werneri. The Madagascan Diplocladus trinotatus (Pic, 1949) is excluded from Diplocladus in this revision; a review of the Madagascan tilline genera is required to determine its correct generic placement. Isocymatodera atricolor (Pic, 1935) new combination, is here removed from Strotocera.